Capítulo 4. Identificación y pronóstico de los ciclos del empleo en Ciudad Juárez, Chihuahua, México - Sánchez-Juárez , Isaac; García-Almada, Rosa María (Crecimiento económico, empleo, innovación y desigualdad regional en México, 2026)
This chapter identifies and forecasts sectoral employment growth cycles in Ciudad Juárez to inform stabilization and development strategies. Using monthly IMSS formal-employment data (1997/08–2023/06) for total employment and key sectors, it extracts cyclical components with the Baxter–King filter and dates expansions and contractions by rule-based thresholds, measuring duration and average monthly depth. It then forecasts employment to 2024/12 with Box–Jenkins ARIMA models and derives predicted cycles. Results show four complete cycles for total employment, with the deepest recession in 2007/10–2009/05; manufacturing mirrors this shock and exhibits the largest depth, while construction is most affected during COVID-19. Policy recommendations emphasize investment, upgrading, and diversification.